Novel strategies to prevent and overcome relapse after allogeneic hematopoietic cell transplantation in acute lymphoblastic leukemia - Hodroj, Mohammad Hassan; Abou Dalle, Iman; Moukalled, Nour; El Cheikh, Jean; Mohty, Mohamad; Bazarbachi, Ali (Frontiers in Immunology, 2023)
The outcome of B-cell acute lymphoblastic leukemia (B-ALL) has improved over time with the incorporation of multi-agent chemotherapy in the treatment landscape as well as the recent approval of immunotherapeutic agents allowing a larger proportion of patients to undergo allogeneic hematopoietic cell transplantation (allo-HCT) which is still considered a potential curative approach. However, relapse post-transplant is still occurring and constitutes a common cause of treatment failure in B-ALL. The present review aims to discuss the novel strategies and therapies used to prevent and overcome relapse post allo-HCT in patients with ALL, focusing on the role of tyrosine kinase inhibitors in Philadelphia chromosome positive B-ALL, the role of innovative agents such as blinatumomab and inotuzumab ozogamicin, and finally the role of cellular therapy.